2006
DOI: 10.4049/jimmunol.177.12.8633
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Cell-Selective Enhancement of HumanIL13Transcription byIL13-1112C>T, a Polymorphism Associated with Allergic Inflammation

Abstract: IL-13 is a central mediator of allergic inflammation. The single nucleotide polymorphism IL13-1112C>T (rs1800925) is associated with allergic phenotypes in ethnically distinct populations, but the underlying mechanism(s) remain unknown. Using in vivo, in vitro, and in silico analysis, we show that the IL13-1112T allele enhanced IL13 promoter activity in primary human and murine CD4+ Th2 lymphocytes. Increased expression of IL13-1112T in Th2 cells was associated with the creation of a Yin-Yang 1 binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 51 publications
4
89
0
2
Order By: Relevance
“…26,27 The SNP IL13 rs1800925 is a functional polymorphism located in the promoter of the gene and the T allele is associated with increased IL13 transcription. 28 In our study, patients harboring the T allele had poorer response to RT-CT. By killing tumor cells, RT-CT promotes the release of tumor-associated antigens, which are then taken up by dendritic cells and presented to cytolytic T cells. This cross-presentation is believed to enhance RT-CT effects.…”
mentioning
confidence: 68%
“…26,27 The SNP IL13 rs1800925 is a functional polymorphism located in the promoter of the gene and the T allele is associated with increased IL13 transcription. 28 In our study, patients harboring the T allele had poorer response to RT-CT. By killing tumor cells, RT-CT promotes the release of tumor-associated antigens, which are then taken up by dendritic cells and presented to cytolytic T cells. This cross-presentation is believed to enhance RT-CT effects.…”
mentioning
confidence: 68%
“…On the other hand, in a larger population of 1073 smokers and former smokers, IL13-1111CT was not associated with lung function measures, and there was a significant combined effect of the promoter SNP IL13-1111CT on percent predicted FEV 1 , suggesting that the genetic variant may modulate the adverse effects of cigarette smoking on pulmonary function (32). In fact, IL13-1112CT has been reported to enhance IL13 activity in vitro (33). The lack of replication of this association in our study may be due to a bias in the selection of healthy smokers.…”
Section: Discussionmentioning
confidence: 96%
“…14 rs1800925 has also been shown to affect the binding of transcriptional factors to the site encompassing this mutation. [14][15][16] A pilot study, performed on the Malian population, failed to detect correlation between rs1800925 and 33 surrounding markers genotyped. 14 These data suggested that rs1800925 may be the functional single-nucleotide polymorphism (SNP) controlling infection levels.…”
Section: Introductionmentioning
confidence: 99%